Réponses

2013-08-11T18:48:55+02:00

     {  2x − 3y  =  1

     {  2x − 2y  =  −1

 

     En soustrayant par partie, on obtient :        (2x − 3y) − (2x − 2y)  =  1 − (−1)

                                                soit                  2x − 3y − 2x + 2y  =  1 + 1

                                                d'où                                       −y  =  2

                                                donc                                        y  =  −2                  

 

    D'où on tire de la première équation que :  2x  =  1 + 3y

                                                                       =  1 + 3(−2)

                                                                       =  1 − 6

                                                                       =  −5

                                                       donc     x  =  −5/2

 

   On a ainsi la solution suivante :   {  x  =  −5/2

                                                   {  y  =  −2

 

     [Vérification :   2(−5/2) − 3(−2)  =  −5 + 6

                                                   =  1

                           2(−5/2) − 2(−2)  =  −5 + 4

                                                   =  −1]